PENGARUH MODEL PEMBELAJARAN VALUE CLARIFICATION TECHNIQUE TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR PADA PELAJARAN PENDIDIKAN PANCASILA - Suci Mar Atul Auliati; Muhammad Syahrul Rizal; Nurmalina; Syahrial; Joni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aimed to examine the effect of the Value Clarification Technique (VCT) learning model assisted by question card media on the critical thinking ability of elementary school students. The research was conducted at UPT SDM 002 Penyasawan involving 36 fifth-grade students divided into two classes. This study employed a quasi-experimental method with a Nonequivalent Control Group Design and a quantitative approach. The instruments used to measure students' critical thinking skills were essay tests and observation sheets. Quantitative data analysis was processed using SPSS version 25. The results showed that students taught using the VCT learning model assisted by question cards had higher critical thinking skills compared to those taught using conventional methods. Based on the independent sample t-test, the significance value obtained was 0.000 < 0.05, with the experimental class scoring an average of 84.67, while the control class scored 76.22. This indicates that the VCT learning model assisted by question cards is more effective in improving students’ critical thinking skills. Thus, this model can be an alternative solution in Pancasila Education learning to develop students’ critical thinking at the elementary level.